2017
DOI: 10.3390/su9112154
|View full text |Cite
|
Sign up to set email alerts
|

Research on Energy-Saving Scheduling of a Forging Stock Charging Furnace Based on an Improved SPEA2 Algorithm

Abstract: Abstract:In order to help the forging enterprise realize energy conservation and emission reduction, the scheduling problem of furnace heating was improved in this paper. Aiming at the charging problem of continuous heating furnace, a multi-objective furnace charging model with minimum capacity difference and waiting time was established in this paper. An improved strength Pareto evolutionary algorithm 2 (SPEA2) algorithm was designed to solve this problem. The original fitness assignment strategy, crossover o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The authors concluded that the model could assist in decision-making to optimize the charge material mixture recipes, thereby decreasing electrical energy costs, which are significant operating expenses in an EAF. He et al [34] proposed fixing the furnace heating schedule issue to assist forging firms in achieving energy efficiency and reducing emissions. This study established a multi-objective furnace charging model to address the charging issue faced by continuous heating furnaces, aiming to minimize capacity difference and waiting time.…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…The authors concluded that the model could assist in decision-making to optimize the charge material mixture recipes, thereby decreasing electrical energy costs, which are significant operating expenses in an EAF. He et al [34] proposed fixing the furnace heating schedule issue to assist forging firms in achieving energy efficiency and reducing emissions. This study established a multi-objective furnace charging model to address the charging issue faced by continuous heating furnaces, aiming to minimize capacity difference and waiting time.…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Consequently, the minimization of emission quantity with a constant emission-to-energy factor leads to a minimization of energy consumption. Energy consumption is also indirectly taken into account in approaches that maximize time in power-saving mode (such as in [22]), minimize unnecessary heating time (e.g., [23]), or minimize unnecessary waiting time on machines to reduce storage energy consumption (e.g., for holding the temperature of hot products, such as in [24]).…”
Section: Ecological Consideration Of Energy Consumptionmentioning
confidence: 99%
“…For example, the authors of [61,71,72] included "holding energy", which equals the energy needed for holding the temperature in induction furnaces until the finished job (i.e., melted metal) is removed. Comparable approaches can be found in [16,23,146]. Ref.…”
Section: Various Energy Utilization Factorsmentioning
confidence: 99%
“…Tis technique helps in generating diverse and uniformly distributed set of solutions. Subsequent studies have further enhanced the solution capability of population SPEA2-based optimization algorithms utilizing immunity algorithms [19][20][21].…”
Section: Introductionmentioning
confidence: 99%